2022
DOI: 10.1021/acs.jmedchem.2c01010
|View full text |Cite
|
Sign up to set email alerts
|

6-Thioguanosine Monophosphate Prodrugs Display Enhanced Performance against Thiopurine-Resistant Leukemia and Breast Cancer Cells

Abstract: Thiopurines are in widespread clinical use for the treatment of immunological disorders and certain cancers. However, treatment failure due to resistance or adverse drug reactions are common, asking for new therapeutic strategies. We investigated the potential of 6-thioguanosine monophosphate (6sGMP) prodrugs to overcome resistance to 6-thioguanine. We successfully developed synthetic routes toward diverse 6sGMP prodrugs, tested their proliferation inhibitory potential in different cell lines, and examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Again, this demonstrates that normal cells may have greater sensitivity to phosph(on) ate prodrug metabolites than tumour cell lines and should be considered when testing cycloSal prodrugs at higher concentrations. 20 The prodrug metabolite concentrations used in this study are within the reported concentration ranges used for phosphoramidate, bis-amidate and cycloSal prodrug compounds during in vitro evaluations. Furthermore, these concentrations are within the reported maximum plasma concentrations of several FDA approved anti-cancer agents.…”
Section: Rsc Medicinal Chemistry Research Articlesupporting
confidence: 54%
See 1 more Smart Citation
“…Again, this demonstrates that normal cells may have greater sensitivity to phosph(on) ate prodrug metabolites than tumour cell lines and should be considered when testing cycloSal prodrugs at higher concentrations. 20 The prodrug metabolite concentrations used in this study are within the reported concentration ranges used for phosphoramidate, bis-amidate and cycloSal prodrug compounds during in vitro evaluations. Furthermore, these concentrations are within the reported maximum plasma concentrations of several FDA approved anti-cancer agents.…”
Section: Rsc Medicinal Chemistry Research Articlesupporting
confidence: 54%
“…15,16 The use of phosph(on)ate prodrugs is expanding, especially to non-nucleotide scaffolds, with compounds being evaluated at micro-molar concentrations during in vitro studies. [17][18][19][20] The metabolites liberated upon activation of the prodrug are rarely taken into account during the evaluation process and are often considered inert. Herein, the current generation of prodrugs, namely the phosphoramidate, bis-amidate and cycloSal prodrugs are evaluated for their potential toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they can act as active ingredients in drugs for the treatment of diseases and as ligands in metal catalytic reactions (Scheme 1a). [1][2][3][4][5][6][7] In the past few decades, various compounds containing phosphorus atoms and other non-phosphorus heteroatoms attached to the same chiral carbon atom have been reported, such as chiral a-hydroxy phosphonates, [8][9][10][11][12] chiral a-amino phos-phonates 13,14 and chiral a-silyl phosphonates. 15 However, the construction of chiral a-boryl phosphonates has not been reported (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a leading disease worldwide, and the projections indicate that the global incidence of cancer will continue to rise [ 1 , 2 ]. The conventional anti-cancer agents are losing their efficiency [ 3 ], highlighting the need to introduce new anti-cancer entities [ 4 , 5 , 6 ]. One strategy to address the issues with existing chemotherapeutics is molecular hybridization: a strategy that generates more efficient therapeutics by combining two (or more) pharmacophores or two (or more) entire drugs in a single hybrid molecule that addresses one or multiple targets [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%